ETIKA PENELITIAN PARIWISATA, PERSPEKTIF TEORI DAN PRAKTIK (Jurnal Ilmiah Pariwisata, 2015)
In tourism research, a researcher may deal with people for data collection such as interviewing and observing people as well as researching physical features which are produced by people such as cultural artifacts. Dealing with people in research means a researcher should understand and implement ethics that can respect people’s rights as human beings. In Indonesia, research ethics may be understood as having consent from the local government to do a research. However, there are many aspects that a researcher should bear in mind when doing research in order to respect respondents’ rights as human beings. This article is based on the writer’s experience in doing tourism research by implementing research ethics. The paper is also a critical review of research ethics by discussing on the importance and the procedures of implementing of research ethics. The paper suggests the importance of understanding and implementing dimensions of research ethics for tourism research including procedural ethics and ethics in practice.